2010
DOI: 10.1002/app.33492
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular weight and testing rate on peel and shear strength of epoxidized natural rubber (ENR 50)‐based adhesives

Abstract: The dependence of peel strength and shear strength of epoxidized natural rubber (ENR-50)-based pressure sensitive adhesive on molecular weight and rate of testing was investigated using coumarone-indene as the tackifying resin. Toluene and polyethylene terephthalate were used as the solvent and substrate respectively, throughout the study. A SHEEN hand coater was used to coat the adhesive on the substrate at a coating thickness of 120 lm. All the adhesion properties were determined by a Llyod Adhesion Tester o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…Studies on adhesive strength of polymers have revealed that there is an optimum molecular weight of polymers at which the optimum combination of adhesive and cohesive forces is achieved that contributes to the highest shear strength. 37,[39][40][41] Since the curing condition remains same for all the formulations, the decrease in performance of the formulation reacted for 180 minutes is most likely due to the properties of uncured adhesive such as viscosity, ow property, and penetration ability.…”
Section: Effect Of Different Parameters On Adhesive Strength Of Et-pementioning
confidence: 99%
“…Studies on adhesive strength of polymers have revealed that there is an optimum molecular weight of polymers at which the optimum combination of adhesive and cohesive forces is achieved that contributes to the highest shear strength. 37,[39][40][41] Since the curing condition remains same for all the formulations, the decrease in performance of the formulation reacted for 180 minutes is most likely due to the properties of uncured adhesive such as viscosity, ow property, and penetration ability.…”
Section: Effect Of Different Parameters On Adhesive Strength Of Et-pementioning
confidence: 99%
“…In order to develop the NR-based PSA, the reduction in molecular weight NR was the main factor that affected the adhesion properties of the PSA [ 18 , 19 , 20 , 21 ]. Therefore, the effect of nip gaps has been first investigated by varying in the range 1–4 mm.…”
Section: Resultsmentioning
confidence: 99%
“…An increase of mastication time led to an increase in the T-peel of NR-PSA/CO for kraft paper, nylon, and Al foil ( Table 3 ). The results suggested that the considerable reduction in the molecular weight of NR during mastication enhanced the adhesion properties of PSA [ 16 , 18 , 19 , 20 ]. Figure 5 shows that there was no residue of NR-PSA/CO appears on all the coating substrates after peeling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the adhesive strength of polymers have demonstrated that a balance of cohesive and adhesive strengths results in stronger adhesion, and the most favorable combination of adhesive and cohesive forces is achieved at an optimum molecular weight of the polymers. Further, the interplay between the molecular weight of polymers and their adhesive strength is governed by the extent of physicochemical interactions and/or crosslinking of polymer chains [ 57 , 100 , 101 , 102 , 103 ]. Additionally, chemical crosslinking generates rigid three-dimensional networks of polymers, and enhances the water resistance property.…”
Section: Chemical Crosslinking: a Key In Enhancing Adhesive Strengmentioning
confidence: 99%